Application of money laundering in corruption cases in maintaining state stability - Mhd. Nasir Sitompul; Ariman Sitompul (The International Journal of Politics and Sociology Research, 2023)
The eradication of corruption must be carried out comprehensively, integrally, and holistically. The commitment of law enforcement in carrying out law enforcement in a firm, consistent, and integrated manner is an important step in order to be able to produce fair law enforcement, provide legal certainty, and benefit the community. These measures can be taken through the implementation of the toughest sanctions for corruption perpetrators, both criminal sanctions, fines, money substitutes, reverse proof by applying money laundering tinfak in every corruption case and coupled with the provision of social sanctions. Contributions are expected to increase public confidence, investors, national self-esteem, and cause a deterrent effect, prevent potential corruptors, optimize the return of state or people's money and maintain state stability.